Corneal Swelling with Cosmetic etafilcon A Lenses versus No Lens Wear. Issue 6 (June 2016) - Moezzi, Amir M.; Varikooty, Jalaiah; Schulze, Marc; Ngo, William; Lorenz, Kathrine Osborn; Boree, Danielle; Jones, Lyndon W.
ABSTRACT: Purpose: To determine if the use of pigments or adding polyvinyl pyrrolidone during the fabrication of 1-DAY ACUVUE DEFINE (AD) brand contact lenses impacts open-eye corneal swelling compared with no lens wear (NLW). Methods: A partial double-masked, randomized, bilateral crossover study was conducted in 24 Asian subjects using AD, 1-DAY ACUVUE DEFINE with Lacreon (ADL), NLW, and a control lens with no tint (1-DAY ACUVUE MOIST [AM]). Central corneal thickness was measured before insertion and immediately after removal after 8 ± 1 h of open-eye wear using an optical pachymeter in one eye. Corneal thickness along a 10-mm cord was measured in the contralateral eye using the Visante optical coherence tomographer (OCT). Corneal swelling was tested for noninferiority using a 5% margin. The endothelial bleb response was measured at baseline and 20 min after lens insertion using specular microscopy. Subjective grading of corneal staining and limbal/bulbar hyperemia were also monitored. Results: After 8 ± 1 h of open-eye wear, central corneal swelling across the study lenses with either optical pachymeter or OCT methods was negligible. Peripheral corneal swelling least-square mean differences with OCT were −0.03% (95% confidence interval [95% CI], −0.65 to 0.58%) and −0.26% (95% CI, −0.87 to 0.36%) between AD and ADL and the control lens (AM), respectively, and 1.67% (95% CI, 1.06 to 2.29%) and 1.45% (95% CI, 0.84 to 2.06%) between AD and ADL and NLW, respectively. No endothelial blebs were observed. No clinically significant differences were distinguished between the lenses and NLW for corneal staining and limbal/bulbar hyperemia. Conclusions: After 8 ± 1 h of open-eye wear, central and peripheral corneal swelling along the horizontal meridian with AD, ADL, AM, and NLW were equivalent. These results confirm that the addition of polyvinyl pyrrolidone or pigments to etafilcon A to obtain a limbal ring design have no impact on corneal swelling or limbal/bulbar hyperemia during normal open-eye wear.